EFEK MEDIASI KEPUASAN KERJA PADA PENGARUH LINGKUNGAN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI KONTRAK (STUDI EKONOMI SUMBER DAYA MANUSIA DI KANTOR BUPATI BAGIAN PEREKONOMIAN DAN PEMBANGUNAN) - Hartawan, I Gusti Made Dharma; Saraswati, Anak Agung Ayu Mas (Komunitas Manajemen Kompetitif, 2023)
The results of this study indicate that the work environment has a direct influence on jobsatisfaction, with the hypothesis that the work environment has a positive and significant effect on jobsatisfaction. Work ability has a direct effect on job satisfaction, with the hypothesis that work abilityhas a positive and significant effect on job satisfaction. The work environment has a direct influence onemployee performance, with the hypothesis that the work environment has a positive and significanteffect on the performance of contract employees. Work ability has a direct influence on employeeperformance, with the hypothesis that work ability has a positive and significant effect on theperformance of contract employees. Job satisfaction has a direct effect on employee performance, withthe hypothesis that job satisfaction has a positive and significant effect on contract employeeperformance.